1986
DOI: 10.1002/tea.3660230406
|View full text |Cite
|
Sign up to set email alerts
|

Performance of students in grades six, nine, and twelve on five logical, spatial and formal tasks

Abstract: Performance on five logical, spatial and formal tasks was used to make inferences about the reasoning structures of the subjects. The tasks used were: seriation matrix, tilt of a cone, location of a point in two and three dimensions, flexible rods and projection of shadows. Three research questions were asked: first, what is the general level of performance; second, are there grade level differences; and third, are there gender differences in task performance. The subjects were 101 middle and high school stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Early research work by psychologists identified two main spatial abilities related to the science education field, visualization—the ability to picture and mentally rotate objects, and orientation—the ability to see objects from a different perspective (Gardner, 1983; McGee, 1979; Newcombe & Dubas, 1992). Prior research in science education has examined these spatial abilities of students in chemistry (Carter, Larussa, & Bodner, 1987; Pribyl & Bodner, 1987; Tuckey & Selvaratnam, 1993), physics (Pallrand & Seeber, 1984), biology (Russell‐Gebbett, 1984), and Earth sciences (Kali & Orion, 1996), in addition to student performance with spatial learning tasks that included psychometric testing of spatial orientation and visualizations (Howe & Doody, 1989; Lord, 1985; Piburn, 1980; Smith & Litman, 1979; Wavering, Perry, Kelsey, & Birdd, 1986). Many of these studies used decontextualized items that were not specific to a particular science discipline or content area.…”
Section: Spatial Thinkingmentioning
confidence: 99%
“…Early research work by psychologists identified two main spatial abilities related to the science education field, visualization—the ability to picture and mentally rotate objects, and orientation—the ability to see objects from a different perspective (Gardner, 1983; McGee, 1979; Newcombe & Dubas, 1992). Prior research in science education has examined these spatial abilities of students in chemistry (Carter, Larussa, & Bodner, 1987; Pribyl & Bodner, 1987; Tuckey & Selvaratnam, 1993), physics (Pallrand & Seeber, 1984), biology (Russell‐Gebbett, 1984), and Earth sciences (Kali & Orion, 1996), in addition to student performance with spatial learning tasks that included psychometric testing of spatial orientation and visualizations (Howe & Doody, 1989; Lord, 1985; Piburn, 1980; Smith & Litman, 1979; Wavering, Perry, Kelsey, & Birdd, 1986). Many of these studies used decontextualized items that were not specific to a particular science discipline or content area.…”
Section: Spatial Thinkingmentioning
confidence: 99%